Respuesta :
Answer:
See below in bold.
Step-by-step explanation:
If we add the 2 equations we eliminate x and we get 2y =2.
So y = 1.
Substituting y = 1 in the second equation 1 = x - 3.
So x = 4.
A. One solution: (4, 1).
If we drew a graph we would have 2 lines which intersect at the point (4, 1).
Answer:
Step-by-step explanation:
If we add the 2 equations we eliminate x and we get 2y =2.So y =1.
Substituting y = 1 in the second equation 1 = x - 3.So x = 4.
A.
One solution: (4, 1).If we drew a graph we would have 2 lines which intersect at the point (4, 1).